SCHOOL-BASED FLOURIDE MOUTH RINSE (S-FMR) SEBAGAI UPAYA PENCEGAHAN KARIES PADA ANAK: SEBUAH TINJAUAN PUSTAKA - Seno, Pratitis Widi; Mardiunti, Ambar Delfi; Putri, Dewi Sartieka; Khoerunisa, Irma; Oktadewi, Fitri Diah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2020)
Background: Dental caries is an infectious microbial disease that begins as demineralization of an inorganic portion of tooth, followed by the destruction of organic parts, leading to cavity formation. Fluoride helps to prevent caries which can be administered systematically or topically. Fluoride mouth rinse has been used in school program to prevent caries.Method: This article aim is to describe the effectiveness of school-based fluoride mouth rinse (S-FMR) as one of the effective methods to prevent caries on children.Discussion: The School-based Fluor Mouth Rinse (S-FMR) program or gargling using fluoride in schools is the use of fluoride as a mouth rinse for children aged 6-18 years conducted in the school environment. Several studies have shown that S-FMR can reduce the prevalence of caries.Conclusion: S-FMR is considered effective in preventing caries due to the simple method, cost-effectiveness, time efficiency, and easily undertaken by the teacher’s supervision